アイスランドノチシツガクテキシゼンカンキョウガクテキトクシツニツイテ - 石川, 輝海 (名古屋学院大学総合研究所, 2008)
The Mid-Atlantic ridge is a volcanically active rise that runs south from the Arctic through Iceland to near Antarctica. For some time, fresh flows of basaltic rock have appeared from the various fissures in ridge. Such flows have been frequently observed on Iceland and other islands along the ridge. At the mid-oceanic ridge, new basaltic ocean floor is created. At a few places the mid-ocean ridge rises above sea level, forming islands, such as Iceland, where basaltic volcanism can be observed. Iceland formed by volcanic activity on the Mid-Atlantic Ridge in late Cenozoic time. departmental bulletin paper